PENGARUH PUBLIC SERVICE MOTIVATION TERHADAP KINERJA PERAWAT DI RUMAH SAKIT BHAYANGKARA KOTA PADANG - Tegar, Tegar Dewantara Putra Riano; Rinaldi; Nio, Suci Rahma; Dwatra, Free Dirga (CAUSALITA : Journal of Psychology, 2023)
This study aims to determine the effect of public service motivation on the performance of nurses at Bhayangkara Hospital, Padang City. This type of research is survey research with quantitative research methods. The subjects in this study were nurses who worked at Bhayangkara Padang Hospital. The sampling technique in this study used a total or saturated sampling technique. The subjects in this study were 75 people. The results of the research from the results of the simple linear regression test show that there is no significant effect between the variable public service motivation and nurse performance. This is based on the regression F value obtained at 1.399 with a P value of 0.241 (P> 0.05) which means that Ha is rejected. Keywords: Nurse performance, public service motivation, nurses.